Kultura strategiczna, czyli o kulturowych uwarunkowaniach polityki zagranicznej i bezpieczeństwa - Wiśniewski, Rafał (Przegląd Strategiczny, 2012)
Reflections on cultural conditioning of foreign and security policy has a long and rich tradition. Its modern expression can be found in the strategic culture studies, which have, during more than three decades, left their mark on the discipline of international relations. During that time, it has been subject to considerable evolution and undoubtedly enriched the workshop for interstate relations analysis. The purpose of this paper is to present history of thought on relations between culture and foreign policy, trace the evolution of strategic culture concept in the discipline of IR and outline some issues which promise to open interesting avenues for further studies in this field.